Green synthesis of metal oxide nanoparticles using plumbago zeylanica root extract, spectrochemical characterization, and antibacterial activity against common pathogen - Humayun Akhter, Syed Md; Naeem, Sajid; Ansari, U. S.; Siddiqui, Vasi Uddin; Bharti, Shambhu Shankar; Ahmad, Shameem; Alam, Md Tanwir; Husain, Dilawar; Patil, A. V. (John Wiley and Sons Inc, 2025)
The root extract of Plumbago zeylanica was used to produce iron oxide (FeO), zinc oxide (ZnO), and copper oxide (CuO) nanoparticles. These metal oxides are easy to produce, inexpensive, and ecologically friendly, with considerable antibacterial activity against common infections. The purpose of this work is to explore a sustainable synthesis method and to investigate the comparative antibacterial activity of these nanoparticles. The nanoparticles were characterized using a variety of techniques, including energy-dispersive X-ray (EDX), transmission electron microscopy (TEM), ultraviolet-visible (UV-vis) spectrophotometry, X-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transform infrared spectroscopy. The XRD patterns revealed the crystalline structures of the produced metal oxide nanoparticles by displaying prominent, intense peaks. Morphological investigation utilizing SEM and TEM techniques revealed the nanoparticles’ shapes and sizes, with an average particle size ranging from 9 to 36 nm. EDX spectra verified the presence of an oxide layer on all three metal oxide nanoparticles. UV-vis and FTIR spectroscopy revealed additional optical characteristics. The antibacterial activities of FeO, ZnO, and CuO nanoparticles were tested using disk diffusion assays against Salmonella enterica, Staphylococcus aureus, and Escherichia coli. The results showed that the antibacterial efficiency of these nanoparticles varied according to the type of bacteria. ZnO nanoparticles had the highest antibacterial activity against both Gram-positive and Gram-negative bacteria, while FeO nanoparticles had the lowest antibacterial efficacy. These data imply that ZnO nanoparticles, in particular, have antibacterial properties.